The Educational Value of the Main Character in Facing Life's Problems in the Novel Sunset and Rosie by Tere Liye - Izmawal Pebriani Nasution; Muji Endah Palupi; Ridwan; Amron Zarkasih Ritonga; Ayu Andini; Juli Yani (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study aims to (1) describe the intrinsic elements that build the novel Sunset Bersama Rosie by Tere Liye and (2) identify the educational values contained in the novel through a literary sociology perspective. This research uses a qualitative descriptive method with an embedded case study design. The data consist of words, phrases, and sentences taken from the novel, collected through reading, note-taking, and literature study techniques. Data validity was ensured through theoretical triangulation, and the analysis employed a dialectical approach to relate literary structure with social reality. The findings show that Sunset Bersama Rosie revolves around the themes of love, compassion, and sacrifice. The story follows Tegar, the main character, who experiences deep emotional struggles following the Bali II bombing in 2005. The settings of Bali, Lombok, and Jakarta enrich the novel’s socio-cultural background. The analysis reveals several educational values reflected in the characters’ behavior and moral development, including the value of peace shown through forgiveness after tragedy, love illustrated in Tegar’s sincere devotion to family and friends, sacrifice embodied by Rosie’s willingness to prioritize others’ happiness, and responsibility demonstrated through the characters’ commitment to face challenges with integrity. These values highlight how the novel not only portrays emotional resilience but also promotes moral awareness and social empathy in readers.